2017
DOI: 10.1371/journal.pone.0174920
|View full text |Cite
|
Sign up to set email alerts
|

Silent dissemination of HTLV-1 in an endemic area of Argentina. Epidemiological and molecular evidence of intrafamilial transmission

Abstract: BackgroundMolecular and epidemiological studies of transmission routes and risk factors for infection by HTLV-1 are extremely important in order to implement control measures, especially because of the high prevalence of HTLV-1 in several regions of the world. San Salvador de Jujuy, Northwest Argentina, is a highly endemic area for HTLV-1 and foci of tropical spastic paraparesis/HTLV-1-associated myelopathy.ObjectiveTo gain further insight into the role of intrafamilial transmission of HTLV-1 in a highly endem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
2
19
0
1
Order By: Relevance
“…HTLV prevalence in central provinces ranged from 0% to 0.2% (0.028-0.26% HTLV-1; 0.007-0.03% HTLV-2) [281,282,284,285,[287][288][289][290][291][292][294][295][296]384]. In contrast, this incidence is increased up to 9.8% of HTLV-1 in Jujuy [280,292,385,386], and to 31.5% when Jujuy family clusters were studied [387]. Surprisingly, other Northern Argentinean cities reported low HTLV positivity, namely 0.16-0.7% in Salta that borders with Jujuy [284,292], 0.6% in Formosa [292] and 0.007% in Misiones [295].…”
Section: Htlv Prevalence and Morbidity In Latin Americamentioning
confidence: 99%
“…HTLV prevalence in central provinces ranged from 0% to 0.2% (0.028-0.26% HTLV-1; 0.007-0.03% HTLV-2) [281,282,284,285,[287][288][289][290][291][292][294][295][296]384]. In contrast, this incidence is increased up to 9.8% of HTLV-1 in Jujuy [280,292,385,386], and to 31.5% when Jujuy family clusters were studied [387]. Surprisingly, other Northern Argentinean cities reported low HTLV positivity, namely 0.16-0.7% in Salta that borders with Jujuy [284,292], 0.6% in Formosa [292] and 0.007% in Misiones [295].…”
Section: Htlv Prevalence and Morbidity In Latin Americamentioning
confidence: 99%
“…Vertical transmission is common and is probably the most important route for the maintenance of HTLV within epidemiologically closed communities, as seen with HTLV-2c among Indians communities in the Amazon area of Brazil and in urban areas [6,33,[42][43][44]. Among the Guaymi in Panama, there are relatively more infected children born from infected mothers [28,45], and among the Kubenkokre, Kayapo villagers in the Amazon region of Brazil, familial cluster studies have showed the transmission of the virus crossing one or more generations, and more than 20% of the children under 9 years of age are infected [6].…”
Section: Introductionmentioning
confidence: 99%
“…Human T-lymphotropic virus 1 (HTLV-1) associated diseases were originally described as sporadic entities, but family clusters have been long reported worldwide ( Ishak et al, 1995 ; da Costa et al, 2013 ; Alvarez et al, 2016 ; Frutos et al, 2017 ). Members of the same family share transmission routes of infection, virus genotypes, host genetic background, and environmental factors that increase the risk for family aggregation of the virus infection and associated diseases.…”
Section: Introductionmentioning
confidence: 99%